Praktik Bisnis yang Dilarang dalam Islam: Perspektif Etika dan Hukum - Nurjannah; Ita Rukmanasari; Prades Ariato Silondae; Rahmawati Muin; Abdul Wahid Haddade (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to outline things that are prohibited in business practices both in formal law and Islamic law. This research includes library research, which uses a form of descriptive analysis. The research results show that in the law the things that are not permitted are monopoly, monopsony, market control and conspiracy. In the Islamic economic system, the cause of a transaction being haram is due to three factors, namely haram substances / haram li-dzatihi (pork, khamr, carrion, blood); haram apart from the substance / haram li-ghairihi (tadlis, gharar, ikhtikar, bai'najasy, usury, maysir, risywah); and the contract is invalid/complete (the pillars and conditions are not fulfilled, ta'alluq occurs, two in one occurs)